Comparative Study of Bulgarian Linden Honey (Tilia sp.) - Anastasiya Yankova-Nikolova; Desislava Vlahova-Vangelova; Desislav Balev; Nikolay Kolev; Stefan Dragoev; Biljana Lowndes-Nikolova (Foods)
The present study aims to evaluate and compare some of the main indicators characterizing Bulgarian linden honey depending on the geographical origin. A total of 18 samples were collected from the six regions of Bulgaria, with 3 samples from each region taken from different producers during the 2023 harvest. The physicochemical indicators: hydroxymethylfurfural content, diastase activity, pH, color, water content and electrical conductivity, as well as organoleptic and pollen characteristics, were analyzed. Antioxidant activity was also investigated by several methods: total phenolic content (TPC), phenolic compounds by the Glories method, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical activity, CUPRAC (Cupric Reducing Antioxidant Capacity), iron-reducing antioxidant capacity (FRAP) assay, and radical scavenging capacity in terms of ABTS•+, ORAC (oxygen radical antioxidant capacity). Differences were found depending on the region. All the studied honeys from the Northern Central Region contained higher Tilia sp. pollen. In the Southwestern Region, Tilia sp. pollen was not detected in any of the honey samples. The highest sensory score was awarded to linden honey from the Northern Central Region. An overall assessment ranks linden honey from the Northern Central region, the richest in linden forests, as the highest quality among the six studied regions. Another key finding was that 39% of linden honey labeled or declared as monofloral linden honey on the Bulgarian market does not meet the established criteria for monofloral honey.